Mitigating poverty and undernutrition through social protection: A simulation analysis of the COVID-19 pandemic in Bangladesh, Myanmar, and Indonesia - Ecker, Olivier; Alderman, Harold; Comstock, Andrew R.; Headey, Derek D.; Mahrt, Kristi; Pradesha, Angga (International Food Policy Research Institute, 2023)
This study addresses the policy-relevant question of how, in the face of major economic shocks, social protection interventions can more effectively mitigate undernutrition. In particular, it considers the scope of scaled-up fortification of staples to avert the “hidden hunger” of micronutrient deficiencies. As a re-cent and still relevant example, it focuses on the kinds of economic shocks brought about by the COVID-19 pandemic which, especially during the first lockdowns of April 2020, resulted in severe job and income losses for the poor and thus reduction and changes in spending, with urban and rural non-farm households typically affected more severely than farm households. However, the findings of this study are relevant for other economic shocks that severely reduce household’s disposable income. In this study, we examine the effects of stylized economic shocks on household incomes in Bangladesh, Myanmar, and Indonesia, with a focus on the difference between recommended and actual consumption of particular foods and nutrients. To this end, we use a novel combination of three integrated models to examine impacts and experiment with different types of social protection interventions. In Bangladesh and Indonesia, these are stylized models of the COVID-19 shock and government lock-downs; in Myanmar, however, we model the economic instability that took place after the February 2021 military takeover, which – in conjunction with COVID-19 impacts – resulted in an estimated 18 percent contraction in GDP (World Bank 2022).